Controlled trial of methylprednisolone pulses and low dose oral prednisone for the minimal change nephrotic syndrome. Issue 6505 (9th November 1985) - Imbasciati, E; Gusmano, R; Edefonti, A; Zucchelli, P; Pozzi, C; Grassi, C; Della Volpe, M; Perfumo, F; Petrone, P; Picca, M
Abstract : In a multicentre, randomised, prospective trial 89 patients (67 children and 22 adults) with the minimal change nephrotic syndrome were treated with three intravenous pulses of methylprednisolone followed by low dose oral prednisone for six months (group given methylprednisolone) or with high dose oral prednisone for four weeks followed by low dose oral prednisone for five months (control group). Five patients in the group given methylprednisolone and one in the control group did not respond initially. The time to response was shorter in children treated with methylprednisolone. No significant differences between the two groups were observed in the number of patients who relapsed or number of relapses per patient per year. Patients given methylprednisolone tended to relapse earlier than patients in the control group. Side effects related to treatment were significantly fewer in the group given methylprednisolone than in the control group. These data suggest that a short course of methylprednisolone pulses followed by low dose oral prednisone is only marginally less effective than a regimen of high dose oral steroids but can improve the ratio of risk to benefit associated with treatment of the minimal change nephrotic syndrome.